Memory Clinics and Day Care Centers in Thessaloniki, Northern Greece: 30 Years of Clinical Practice and Experience - Tsolaki, Magda; Tsatali, Marianna; Gkioka, Mara; Poptsi, Eleni; Tsolaki, Anthoula; Papaliagkas, Vasileios; Tabakis, Irene-Maria; Lazarou, Ioulietta; Makri, Marina; Kazis, Dimitrios; Papagiannopoulos, Sotirios; Kiryttopoulos, Andreas; et al. (Frontiers in Neurology, 2021)
Background: This review describes the diagnostic and interventional procedures conducted in two University Memory Clinics (established network of G. Papanikolaou Hospital: 1988-2017 and AHEPA hospital: 2017-today) and two Day Care Centers (established network of DCCs: 2005- today) in North Greece and their contribution in the scientific field of dementia. The aim of this work is 1) to provide a diagnosis and treatment protocol established in the network of Memory Clinics and DCCs and 2) to present further research conducting in the aforementioned network during the last 30 years of clinical practice. Methods: The guidelines to set a protocol, demand a series of actions: 1) Set the diagnosis criteria, neuropsychological assessment, laboratory examinations, examination of neurophysiological, neuroimaging, CSF, blood, and genetic markers. 2) Apply non-pharmacological interventions according to the patient’s needs and specialized psychosocial interventions to patient’s caregivers. Results: In addition to the guidelines followed in Memory Clinics at the 1st and 3rd Departments of Neurology, and two DCCs, a patient’s data base, educational programs and further participation in international research programs, including clinical trials, make strong our contribution in dementia field. Conclusion: In the current paper, we provide useful guidelines on how major and minor neurocognitive disorders are being treated in Thessaloniki- Greece, describing successful practices which have been adapted the last 30 years.